Population attributable risk of key modifiable risk factors associated with non-exclusive breastfeeding in Nigeria - Felix Akpojene Ogbo; Andrew Page; John Idoko; Kingsley E. Agho (BMC, 2018)
Abstract Background Non-exclusive breastfeeding (non-EBF) is a risk factor for many of the 2300 under-five deaths occurring daily in Nigeria - a developing country with approximately 40 million children. This study aimed to quantify and compare the attributable burden of key modifiable risk factors associated with non-EBF in Nigeria to inform strategic policy responses and initiatives. Methods Relative risk and exposure prevalence for selected modifiable risk factors were used to calculate population attributable fractions based on Nigeria Demographic and Health Surveys data for the period (1999-2013). Scenarios based on feasible impact of community-based interventions in reducing exposure prevalence were also considered to calculate comparative potential impact fractions. Results In Nigeria, an estimated 22.8% (95% Confidence Interval, CI: 9.2-37.0%) of non-EBF was attributable to primary and no maternal education; 24.7% (95% CI: 9.5-39.5%) to middle and poor household wealth, 9.7% (1.7-18.1%) to lower number (1-3) and no antenatal care visits; 18.8% (95% CI: 6.9-30.8%) to home delivery and 16.6% (95% CI: 3.0-31.3%) to delivery assisted by a non-health professional. In combination, more than half of all cases of non-EBF (64.5%; 95% CI: 50.0-76.4%) could be attributed to those modifiable risk factors. Scenarios based on feasible impacts of community-based approaches to improve health service access and human capacity suggest that an avoidable burden of non-EBF practice of approximately 11% (95% CI: -5.4; 24.7) is achievable. Conclusion Key modifiable risk factors contribute significantly to non-EBF in Nigerian women. Community-based initiatives and appropriate socio-economic government policies that specifically consider those modifiable risk factors could substantially reduce non-EBF practice in Nigeria.